Accurate querying of frequent subgraphs in power grid graph data - Aihua Zhou; Lipeng Zhu; Xinxin Wu; Hongbin Qiu (Global Energy Interconnection, 2019)
With the development of information technology, the amount of power grid topology data has gradually increased. Therefore, accurate querying of this data has become particularly important. Several researchers have chosen different indexing methods in the filtering stage to obtain more optimized query results because currently there is no uniform and efficient indexing mechanism that achieves good query results. In the traditional algorithm, the hash table for index storage is prone to “collision” problems, which decrease the index construction efficiency. Aiming at the problem of quick index entry, based on the construction of frequent subgraph indexes, a method of serialized storage optimization based on multiple hash tables is proposed. This method mainly uses the exploration sequence to make the keywords evenly distributed; it avoids conflicts of the stored procedure and performs a quick search of the index. The proposed algorithm mainly adopts the “filter-verify” mechanism; in the filtering stage, the index is first established offline, and then the frequent subgraphs are found using the “contains logic” rule to obtain the candidate set. Experimental results show that this method can reduce the time and scale of candidate set generation and improve query efficiency. Keywords: Power grid, Graph database, Graph computing, Multi-Hash table, Frequent subgraphs